Analisis Kinerja Anggaran Pendapatan dan Belanja Daerah Kota Batu Tahun 2017-2021 - Magviroh, Oktavia Maimatul; Diana, Nur; Nandiroh, Umi (e_Jurnal Ilmiah Riset Akuntansi, 2023)
The aim of this study is to analyze the performance of the Income and Purchase Budget of the Batu City Region in 2017-2021. This research uses a quantitative descriptive method, with data in the form of secondary data, namely, the 2017-2021 Budget Revenue and Shopping Report of the Batu City Region obtained from the Financial and Asset Authority of the Town of Stone. The data was then analyzed using the regional financial independence ratio, the regional real income efficiency ratio and the local financial capacity ratio. The results of the study showed that the financial performance of the Regional Revenue and Purchasing Budget for 2017-2021 is based on the average ratio of financial independence of the regions of 20.35% with category less, the average rate of efficiency of the original income of the areas of 111.11% with the category very effective, the mean rate of effectiveness of the local income of 91.35% for the category less efficient, and the average proportion of regional financial capacity of 16.702% with the Category less.Keywords: Regional revenue and expenditure budget, financial performance, independence, effectiveness, efficiency, financial capabilities.